Letter (copy) : re Autochir conveyer - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0086-001 16th November, 1937. C. Holock, Esq., The Finance Officer, The Civil Service Clerical Association, 2, Upper Belgrave Street, London, S.W.1. Dear Mr. Holock, re AUTOCHIR CONVEYOR. In reply to your further letter regarding the gift of this specially designed vehicle - an Autochir Conveyor - by the members of the Civil Service Clerical Association to the Spanish Medical Aid Committee for use on the Government side in the Spanish Civil War, I am writing on behalf of the Committee to express our pleasure at the gift. The cost of the specially designed vehicle will be about £550, and the Spanish Medical Aid Committee are fitting into the vehicle a special X-ray transportable apparatus and a very special electric lifting generator. The vehicle, as I explained, will accompany the Surgical autochir of the Mobile Surgical Unit. The Autochir will hold the Medical equipment and the Autochir Conveyor will have all the necessary extra equipment, such as X-ray, electric light and power plant, the Triage arrangements (arrangements for pre-operative attention of patients, recording of wounds names ), etc. The Spanish Medical Aid Committee will be delighted to make arrangements for a Tablet to be placed on the vehicle proclaiming the vehicle as a gift from your Organisation and for a ceremonial handing over of the vehicle by you to the Spanish Medical Aid Committee. The vehicle will shortly be ready and I will be glad to receive the amount so kindly contributed by your Association. If I can give you any further information please let me know. Yours faithfully, 292C/946/2/86